Determination of optimal parameters technological process of polling of copper wire with alloy POS-61 - V. V. Aleksandrova; M. V. Kuzmin; A. O. Patianova; V. L. Semenov; R. I. Alexandrov (Chimica Techno Acta)
The development of the technique for the manufacture of round copper wire coated with "tin-lead" alloy is considered. The optimal parameters such as the temperature of the "tin-lead" alloy melt, the linear speed for tinning of the wire with a round copper alloy and the diameter of the diamond die were determined. The test results of the experimental wire samples are presented.